Smart textile based optical sensing for health care - Ballaji, Hattan Khaled Y. (2021)
In healthcare, the photoplethysmogram (PPG) is an optical measurement of the changes in blood volume in tissue. PPG systems can be used to monitor key physiological parameters comfortably and unobtrusively, such as heart rate (HR), peripheral oxygen saturation (SpO2) and capillary refill time (CRT). Plastic optical fibre (POF) is widely used in various applications. Its harmless properties, robustness and flexibility make this material safe to use on the skin [1]. Thus, it has the potential to be wearable and integrated into textile systems. This research work investigates the development of PPG systems based on POF to provide reliable measurements of HR, SpO2 and CRT. To design a reliable PPG sensor, it needs to be tested on humans. However, in human biological systems, it is difficult to control physiological factors (e.g. breathing and body temperature) and motion artefacts during measurements, which make it challenging to validate the PPG measurements. Therefore, in this thesis, a tubular cardiovascular flow phantom system was developed to simulate the human circulatory system in order to obtain robust PPG signals. The results demonstrated a stable pulsatile signals with no effect from physiological factors compared with a human. This indicates that the phantom flow system provides potentially a robust controlled environment for validating a PPG sensor. In the application of photoplethysmography to humans, signal loss due to the position of the sensor can be a problem, particularly in life preserving applications. Accordingly, in this thesis, a system was investigated based on multi-channel optical fibre sensor probes integrated into a textile sleeve. The system used two wavelengths (660 nm and 830 nm due to the absorption spectra of oxygenated and deoxygenated haemoglobin are different) to obtain two PPG signals, which were then utilised to calculate SpO2. Four POF sensors were used to increase the likelihood of obtaining a high-quality PPG signals without adjusting the position of the garment. They were integrated into a stretchable textile sleeve to ensure that the sleeve was in contact with the skin and to reduce the motion artefacts. The most significant finding to emerge from the tests on 10 healthy volunteers was that, in all cases, the system can provide an SpO2 % value in at least one of the four sensors without adjusting the sleeve. This could not be achieved when only using a single PPG sensor which might need adjustments in order to obtain a robust signal. Comparing the SpO2 readings obtained from the multi-channel sensor to those obtained from a reference commercial oximeter showed that the mean difference (bias) between them was -0.03%, the upper and lower limits of agreement (LOA) were 0.52% and -0.58%, respectively. This multi-channel sensor has potential to achieve reliable, unobtrusive and comfortable textile-based monitoring of both HR and SpO2 during daily life. The capillary refill time (CRT) is often used on an individual’s foot to evaluate tissue breakdown that may cause foot ulcers, especially in people with diabetes. For CRT measurements, applied and released pressure play a significant role in evacuating and refilling the capillaries. Therefore, the novelty of this work is also to design an optical fibre sensor probe combining POF and fibre Bragg grating (FBG – silica fibre type) sensors to simultaneously measure the reflected blood volume changes and the skin contact pressure, respectively, on the sole of a foot. One POF transmits light and one POF detects the light to and from the skin. The wavelength of 530 nm was used because it can provide a high contrast signal in comparison to other illumination of LEDs wavelengths. The FBG layer contained two FBGs; both (FBG1, FBG2) were surrounded by an epoxy layer but one (FBG2) was also embedded in a stainless steel tube. FBG1 was used to detect the applied pressure and FBG2 acted as a temperature reference. The CRT was figured out after normalising and polynomial curve fitting the measured signal. The results from 10 healthy volunteers showed that the blanching pressure was 100.76 ± 4.78 kPa (mean and standard deviations) and the refilling pressure (weight of the foot itself) was 7.19 ± 1.16 kPa. The average CRT was 1.38 ± 0.48 seconds and the stable blood volume time was 4.77 ± 1.57 seconds. The combined sensor helped increase the reliability and accuracy of the CRT measurements.